2007
DOI: 10.1021/ma070251t
|View full text |Cite
|
Sign up to set email alerts
|

SAXS Study of Oriented Crystallization of Polypropylene from a Quiescent Melt

Abstract: Uniaxially oriented polypropylene (PP) is molten in the synchrotron beam and crystallized from the quiescent melt, keeping its orientation in order to study the mechanisms of its crystallization. We document the different nanostructures observed as a function of melt-annealing temperature, undercooling, and time. In order to obtain a melt that crystallizes with high preferential orientation again, a melt-annealing temperature between 170 and 176 °C is chosen. Isothermal crystallization at 155 °C results in slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…This is readily explained by the correlation among the crystalline bridges in equatorial direction. 43 These observations support a finding from a previous study 43 which indicated that the cross-hatched lamellae of PP are a secondary feature of its crystallization. We admit that this observation should be verified by a corresponding WAXS study.…”
Section: Nanostructure Differences As Deduced From the Cdfsupporting
confidence: 84%
“…This is readily explained by the correlation among the crystalline bridges in equatorial direction. 43 These observations support a finding from a previous study 43 which indicated that the cross-hatched lamellae of PP are a secondary feature of its crystallization. We admit that this observation should be verified by a corresponding WAXS study.…”
Section: Nanostructure Differences As Deduced From the Cdfsupporting
confidence: 84%
“…The scattering of the undrawn material is presented in the upper left corner. It shows the typical scattering of semicrystalline polypropylene with uniaxial orientation [22, 37, 38]. When unblended thermoplasts are sheet-extruded but not drawn, such a morphology is well known and called a precursor of a hard-elastic material [35].…”
Section: Resultsmentioning
confidence: 99%
“…In the interval 3 < t < 4.5 min, the WAXS exhibits the equilibrium-dominated regime of the crystallization. Here the SAXS, 15 ( Figure 9) detects a stable block structure of midrange correlation in both fiber and lateral directions. For t > 4.5 min, the WAXS peak-integral curves, S(t) and S*(t), indicate the growth-dominated regime of the crystallization.…”
Section: Crystallization At 145°cmentioning
confidence: 91%
“…Therefore, the period before the start of the nucleation (equilibrium-dominated crystallization) has not been resolved by the SAXS. The SAXS recorded during the regime of equilibriumdominated crystallization has shown a 3D arrangement 15 ( Figure 7) of blocks (i.e., nuclei) that turn from an entwined arrangement into a checkered arrangement, while at the same time, the gaps between the blocks shrink in both lateral and longitudinal directions. Because the WAXS shows that there is not much increase in crystallinity, the SAXS results could be explained by the notion that during the equilibrium-dominated crystallization, the amplitude of the size fluctuation of the nuclei appears to increase.…”
Section: Crystallization At 145°cmentioning
confidence: 99%
See 1 more Smart Citation